Ninth Five Year Plan 1997-2002 and Annual Plan-1997-98 Draft Proposals Volume II Part - X - 'D' Social Services Government of Meghalaya - Planning Commission (Planning Commission, 1997)
It is proposed to strengthen the State Vocational Training Wing of the Directorate to cope with the expanding works of the Directorate with the expansion of Industrial Training Institutes in the State. The Scheme proposed during 1995-96 and is also proposed to spill over to the Ninth Plan.
Government of Meghalaya